1987
DOI: 10.1007/bf01290505
|View full text |Cite
|
Sign up to set email alerts
|

Does the phenomenon of anomalons really exist?

Abstract: An analysis of experimental data available to the date and concerning the dependence of projectile fragments (PFs) mean free path (mfp) in heavy-ion collisions on the distance from the point of their emission is presented. The linear dependence of the relative variation of the estimates of the mfp on l/N, where N is the number of PFs observed, has been established. This dependence seems to be understood only from the statistical point of view. It has been shown that the idea of the absence of anomalons in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…They are secondary fragments with anomalously large interaction cross sections, and it is suggested that roughly 5% of all fragments could be anomalons with cross sections which maybe four times that of conventional nuclear matter. For a useful discussion of the anomalon effect see the paper by Pshenin and Voinov [6].…”
Section: Pacsmentioning
confidence: 99%
“…They are secondary fragments with anomalously large interaction cross sections, and it is suggested that roughly 5% of all fragments could be anomalons with cross sections which maybe four times that of conventional nuclear matter. For a useful discussion of the anomalon effect see the paper by Pshenin and Voinov [6].…”
Section: Pacsmentioning
confidence: 99%